V2G application to frequency regulation in a microgrid using decentralized fuzzy controller - Janfeshan, K.; Masoum, Mohammad Sherkat; Deilami, Sara (IEEE, 2014)
Frequency regulation is one of the main issues in power grids. Any load-generation imbalance that occurs in a power network, causes the frequency to deviate from its nominal value. During such transient conditions it is important to use a method to decrease frequency fluctuations and recover the power quality to network normal condition as quickly as possible. There are several solutions for frequency regulation. One of them is to use energy storage system (ESS) capacity to compensate the power shortage and load disturbances. Electric vehicles (EVs) can be seen as a mobile and controllable storage unit and the battery capacity can be used as a backup for power networks. The reverse flow of energy from vehicle to grid (V2G) can participate in frequency regulation. This paper presents a distributed fuzzy logic control (FLC) design for V2G application in frequency regulation. With FLC the power flow from the EVs to the grid is adjusted based on regulation demand and state of charge (SOC) of the vehicle battery.